PERAN PEREMPUAN DALAM NOVEL ATHIRAH KARYA ALBERTHIENE ENDAH - Adhani, Agnes; Puspitasari, Yeni (Educatio Vitae, 2015)
This research aims to know and explain the characters, plot, setting, theme, and the role of women which covers three aspects, namely the education of women, the position of the woman in the family, and the role of the social character of women in society. Use a descriptive qualitative approach. Data source: Endah Alberthiene Athirah novel works. Characterizations: Athirah, Kerra, Mufidah, Jusuf Kalla, Haji, and Mohamad. The depiction of the character of the offender/figure using the techniques ekspositori and dramatic. Plot: plot mix. The setting of the place took place in Makassar. The setting time of incident at dawn, noon, afternoon, and evening in 1920-1970. A major theme in the novel is the struggle of a woman dipoligami. A minor theme is patience and sincerity, kindness his wife, struggle, love and family. Athirah and Kerra gets informal education, Mufidah get formal education and informal education. The position of the woman in the family as a son, wife, and mother of his children. Athirah is a very obedient son. A very obedient son Kerra. Mufidah and the very diligent. Athirah a wife who loves her husband, she continued to fight polygamy victims although finally defeated and resigned. Kerra are a wife to her husband, she was a victim of polygamy since resigned to accept the situation. Mufidah a wife who always supports the decision of her husband, she was the girl's anti polygamy. Athirah deeply loved his children. Kerra a mother loves her children. Mufidah is concerned his children. The social role of the woman in society: active women figures Athirah follow activities. Kerra not addressed. Mufidah involved in the wedding of his friend. Keywords: characters, plot, setting, theme, the role of women